2017
DOI: 10.1017/s1047951117000798
|View full text |Cite
|
Sign up to set email alerts
|

Flail anterior tricuspid valve leaflet in a neonate: association with maternal antiphospholipid syndrome

Abstract: This brief report describes a case of flail anterior tricuspid valve leaflet in a neonate associated with maternal antiphospholipid syndrome. Fetal echocardiography at 27 weeks of gestation showed competent atrioventricular valves with biventricular echogenic chordae. Fetal distress was noted at delivery, and echocardiography showed a flail anterior leaflet of the tricuspid valve with severe regurgitation. Possible causation and implications of maternal antiphospholipid syndrome are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A total of 12 cases of acute valvar rupture attributable to antenatal exposure to maternal autoantibodies were analyzed ( Table 1 ). This includes Case A from our experience (numbered as Case 1) and 11 patients extracted from 10 reports (numbered Cases 2–10) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Shiraishi et al reported cases of acute MR in infants, of which two cases were attributable to maternal autoimmunity [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 12 cases of acute valvar rupture attributable to antenatal exposure to maternal autoantibodies were analyzed ( Table 1 ). This includes Case A from our experience (numbered as Case 1) and 11 patients extracted from 10 reports (numbered Cases 2–10) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Shiraishi et al reported cases of acute MR in infants, of which two cases were attributable to maternal autoimmunity [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 42% (5/12) of mothers (Cases 2–4, 8, and 12) had known autoimmune disease [ 9 , 10 , 16 , 17 ], specifically Sjogren’s syndrome, affecting two mothers (Cases 3 and 4) [ 10 , 17 ]. Two mothers had previously affected children (Cases 3 and 7) [ 10 , 16 , 17 ] and one had a sibling that was affected subsequently (Case 10) [ 14 ]. Three mothers had normal pregnancies prior to the affected fetus (Cases 1,2, and 12) [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations